Rousseau meets Azuma: A Fictional Discourse on the ‘General Will 2.0’ - Roth, Martin; Schäfer, Fabian (MINIKOMI: Austrian Journal of Japanese Studies, 2021)
An imagined conversation between Azuma Hiroki and an old man (maybe Jean-Jacques Rousseau) regarding their ideas about "Social Contract" and "General Will 2.0".